The PJSC “Novatek” activity efficiency reserves identification based on the economic and accounting analysis - D. V. Lysenko; L. Akgün (Вестник университета)
A comparative analysis of three large Russian companies – PJSC “Novatek”, PJSC “Gazprom”, PJSC “Surgutneftegaz”, – is presented. The study relevance is caused by the gas industry strategic importance of the country as a whole as well as the specifics of its current situation: a large-scale drop of world gas prices, the ruble depreciation in relation to the US dollar, the introduction of sanctions on Russia. The financial and economic activities of the company PJSC “Novatek” is examined in the article. Various approaches to the analysis and identification of the company’s activities potential are studied. The investment attractiveness of competitors’ companies is evaluated. The research methodology included: complex, empirical, retrospective types of analysis (since the calculations of the companies’ financial conditions indicators are based on their consolidated financial statements data as of December 31, 2015); comparative, horizontal and vertical types of analysis; grouping method is categorization. As a result methodological principles of carrying out an economic analysis of gas producing companies’ activities are formed in order to make effective management decisions in conditions of risk and uncertainty.